The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1462-2920.13602
|View full text |Cite
|
Sign up to set email alerts
|

Root isoflavonoids and hairy root transformation influence key bacterial taxa in the soybean rhizosphere

Abstract: Rhizodeposits play a key role in shaping rhizosphere microbial communities. In soybean, isoflavonoids are a key rhizodeposit component that aid in plant defense and enable symbiotic associations with rhizobia. However, it is uncertain if and how they influence rhizosphere microbial communities. Isoflavonoid biosynthesis was silenced via RNA interference of isoflavone synthase in soybean hairy root composite plants. Rhizosphere soil fractions tightly associated with roots were isolated, and PCR amplicons from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Bacteria in the Comamonadaceae and/or Microbacteriaceae may possess genes that allow them to use daidzein as a carbon source. Comamonadaceae are common in the soybean rhizosphere (Hamid et al, ; White et al, ), with >10% relative abundance (Figure S9). This family contains plant growth promoting bacteria such as Delftia sp., which enhance nodulation and pulse yield when co‐inoculated with Bradyrhizobium elkanii (Cagide, Riviezzi, Minteguiaga, Morel, & Castro‐Sowinski, ), and Variovorax paradoxus , a soybean endophyte with characteristics related to plant growth promotion (Lopes, Carpentieri‐Pipolo, Oro, Pagliosa, & Degrassi, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria in the Comamonadaceae and/or Microbacteriaceae may possess genes that allow them to use daidzein as a carbon source. Comamonadaceae are common in the soybean rhizosphere (Hamid et al, ; White et al, ), with >10% relative abundance (Figure S9). This family contains plant growth promoting bacteria such as Delftia sp., which enhance nodulation and pulse yield when co‐inoculated with Bradyrhizobium elkanii (Cagide, Riviezzi, Minteguiaga, Morel, & Castro‐Sowinski, ), and Variovorax paradoxus , a soybean endophyte with characteristics related to plant growth promotion (Lopes, Carpentieri‐Pipolo, Oro, Pagliosa, & Degrassi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil type primary influences the assemblage of rhizosphere microbial communities (Liu et al, ; Xiao et al, ), and Comamonadaceae was abundant in the rhizosphere of successive soybean‐monoculture cropping (Hamid et al, ), which is concordant with our findings using soils from soybean field under continuous cropping. It should also be noted that daidzein is not the only metabolite to promote the abundance of Comamonadaceae in the soybean rhizosphere, because the silencing of IFS gene in soybean hairy roots resulted in the slight increase of Comamonadaceae in the rhizosphere of IFS‐silenced roots (White et al, ). A synthetic community‐based approach to the daidzein‐mediated interaction among soybean, Comamonadaceae, and other bacteria could identify the molecular basis of these interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuzyakov et al [64] reported that rhizodeposits supply energy to soil microbes for solubilization of organic nitrogen and other nutrients in soil organic matter. White et al [78] reported that isoflavonoids are vital rhizodeposits that help in plant defense and also facilitate symbiotic events with Rhizobia in soybean.…”
Section: Rhizodepositionmentioning
confidence: 99%
“…The rhizosphere, which is defined as a thin soil layer close to the root system and is actively influenced by metabolic activity [7], has often been used as the preferential site for the isolation of PGPB with potential applications as biofertilizers [8,9]. The habitat of rhizospheric soils differs physically, chemically and biologically from the nonrhizospheric soils (or bulk soil) because of the continuous release of a complex array of organic-based molecules such as rhizodeposits [10,11]. Qualitative and quantitative variations in rhizodeposits are thought to play an active role in shaping the rhizosphere microbiome by enriching population sizes of microbial representatives with competence to consume released compounds according to the plant genotype, age and local environmental conditions [12,13].…”
Section: Introductionmentioning
confidence: 99%